Assessment of Women’s Knowledge about Health Promotion after Cesarean Delivery at Maternity and Pediatric Hospital in Al-Samawa City - Hameed, Hanan; Miran, Najmah (Iraqi National Journal of Nursing Specialties, 2021)
Objective(s): To assess women’s knowledge about health promotion after a cesarean delivery and to determine the association between women’s knowledge and their demographic data of age, level of education, and monthly income.Methodology: A descriptive design is carried out to assess women’s knowledge about health promotion after cesarean delivery at Maternity and Pediatric Hospital in Al-Samawa City. This study starts from 26th of September 2020 up to 16th March 2021. Sample of (100) woman who are at reproductive age, pregnant (prime or multipara) who have planned to have birth by elective cesarean section or had previous elective caesarian section without medical indication or women who had cesarean section with medical indication or emergency.Results: Results of the study show moderate mean of scores for most questions are moderate significance and others questions shows low mean of scores for most questions.Recommendations: The study recommends providing instructions for pregnant women by nurses and midwives about promotion of health after a cesarean delivery. Apply knowledge for gestation women will be counseled by nurses and midwives during the antenatal cycle about childbirth procedures, symptoms, characteristics, and risks, allowing women to make their own decisions through primary health care centers.